Tiber delta CO2‐CH4 degassing: A possible hybrid, tectonically active Sediment‐Hosted Geothermal System near Rome. Issue 1 (16th January 2016) - Ciotoli, G.; Etiope, G.; Marra, F.; Florindo, F.; Giraudi, C.; Ruggiero, L.
Abstract: Fiumicino town in the Tiber River delta, near Rome International Airport (Italy), is historically affected by large amounts of carbon dioxide (CO2 ) in the ground and gas eruptions triggered by shallow drilling. While it is known that CO2 originates from carbonate thermometamorphism and/or mantle degassing, the origin of methane (CH4 ) associated with CO2 is uncertain and the outgassing spatial distribution is unknown. Combining isotope gas geochemistry, soil gas, and structural‐stratigraphic analyses, we provide evidence for a hybrid fluid source system, classifiable as Sediment‐Hosted Geothermal System (SHGS), where biotic CH4 from sedimentary rocks is carried by deep geothermic CO2 through active segments of a half‐graben. Molecular and isotopic composition of CH4 and concentration of heavier alkanes (ethane and propane), obtained from gas vents and soil gas throughout the delta area, reveal that thermogenic CH4 (up to 3.7 vol% in soil gas; δ 13 CCH4 : −37 to −40‰ VPDB‐Vienna Peedee Belemnite, and δ 2 HCH4 : −162 to −203‰ VSMOW ‐ Vienna Standard Mean Ocean Water in gas vents) prevails over possible microbial and abiotic components. The hydrocarbons likely result from known Meso‐Cenozoic petroleum systems of the Latium Tyrrhenian coast. Overmaturation of source rocks or molecular fractionation induced by gas migration are likely responsible for increased C1 /C2+ ratios. CO2 and CH4 soil gas anomalies are scattered along NW‐SE and W‐E alignments, which, based on borehole, geomorphologic, and structural‐stratigraphic analyses, coincide with active faults of a half‐graben that seems to have controlled the recent evolution of the Tiber delta. This SHGS can be a source of considerable greenhouse gas emissions to the atmosphere and hazards for humans and buildings. Key Points: Hybrid inorganic CO2  + biotic CH4 degassing system in the Tiber delta Thermogenic CH4 (and CO2 + alkanes) transported by geothermal CO2 crossing a petroleum system Degassing occurs along neotectonic fault systems forming the Fiumicino half‐graben